2021
DOI: 10.1051/e3sconf/202127310036
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT of distance learning on student mental health in the COVID-19 pandemic

Abstract: Education is one of the industries significantly affected by the novel coronavirus infection (COVID-19) pandemic. Whole countries and cities were isolated, public and private institutions ceased their activities, and the country's higher educational institutions were forced to stop full-time education and switch to distance learning. Thus, the purpose of this study was to compare the indicators of the mental state (depression, anxiety) of students during full-time and distance learning. The first study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…During the COVID-19 pandemic in Jordan, (2021) found that healthcare students had a low degree of health-related quality of life. Lyubetsky et al (2021) assesses indicators such as academic performance satisfaction, depression severity, and anxiety symptoms. The findings revealed that the prevalence of depression and anxiety symptoms among students was considerably greater throughout the distant learning period when compared to similar indicators obtained during full-time education.…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic in Jordan, (2021) found that healthcare students had a low degree of health-related quality of life. Lyubetsky et al (2021) assesses indicators such as academic performance satisfaction, depression severity, and anxiety symptoms. The findings revealed that the prevalence of depression and anxiety symptoms among students was considerably greater throughout the distant learning period when compared to similar indicators obtained during full-time education.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the prevalence of depressive symptoms and anxiety among students was higher during distance learning, compared with similar results obtained during full-time education. Moreover, the research results showed that the sudden transition from one learning environment to another was a major cause of chronic stress, which led to a high prevalence of depressive symptoms and anxiety among students (Lyubetsky et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous study, most students manifested different levels of perceived e-learning stress (36) that could affect online learning readiness. Another study also showed that the prevalence of depressive symptoms and anxiety among students was signi cantly higher during the distance learning period compared to the full-time study period (37). At the same time, female students showed higher education-related stress levels than males (38)(39)(40).…”
Section: Sociodemographic Factorsmentioning
confidence: 94%